Alternative governance arrangements for modular water infrastructure: An exploratory review. Issue 1 (March 2018) - Pakizer, Katrin; Lieberherr, Eva
This article presents an exploratory review of alternative governance arrangements for modular systems in the urban water sector in terms of policy instruments, organizational structure, and underlying mechanisms. We develop an analytical framework to review the literature on alternative arrangements for innovative technologies. The preliminary results highlight the importance of governmental involvement and formal policy instruments to ensure public and environmental health in the context of modular water infrastructures. This is in line with the status quo of conventional water governance arrangements. However, the findings also suggest that informal instruments supplement the formal ones and that instead of political-administrative accountability more horizontal mechanisms, such as answerability toward citizens and consumers, play an important role in the context of new water technologies.